Simple recycling of biowaste eggshells to various calcium phosphates for specific industries - Nongnuch Laohavisuti (Nature Portfolio, 2021)
Abstract Egg consumption is very high throughout the world and with it comes enormous amount of waste eggshells. To reduce and utilize these wastes, eggshell wastes were simply transformed to low- or high-purity calcium carbonate grades by washing, crushing, and drying to use as raw materials for producing highly valuable calcium phosphate products. Low-purity calcium carbonate grade was used to prepare triple superphosphate for using in fertilizer industry, whereas high-purity calcium carbonate grade was used to produce dicalcium phosphate dihydrate, monocalcium phosphate monohydrate, and tricalcium phosphate for using in mineral feed and food additive industries. All calcium phosphate samples obtained by simple, rapid, cheap, and environmentally safe method using eggshells and phosphoric acid were identified and their structural phases and impurities were determined by XRF, XRD and FTIR techniques. Thermal behaviors of raw materials and the prepared calcium phosphates excepted tricalcium phosphate were investigated by TG/DTG techniques. The methodologies described here will be useful to manage eggshells by converting them to highly valuable products, which can solve eggshell wastes problem from industries and communities. This finding supports the viewpoint of zero waste operation to produce value-added products for obtaining sustainable development, which may be selected as an alternative way for material recycling and waste management in the future.